2014
DOI: 10.1007/s00246-014-1033-0
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Tracking and Myocardial Tissue Imaging in Infant of Diabetic Mother with Gestational and Pregestational Diabetes

Abstract: The aim of this study was to evaluate the myocardial changes in infants of diabetic mother either with gestational or pregestational diabetes and its relation to maternal diabetic control. The study included 45 infants of diabetic mother (IDMs) and 45 healthy newborn as a control group. IDMs were then categorized into 2 subgroups: twenty infants of mother with pregestational diabetes and twenty-five infants of mothers with gestational diabetes. The studied groups underwent measurement of the maternal and neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 21 publications
8
65
2
1
Order By: Relevance
“…Tissue Doppler was able to detect both systolic and diastolic dysfunction than conventional Doppler in infants of diabetic mothers with hypertrophic cardiomyopathy when compared to the control group. This higher sensitivity of tissue Doppler over the conventional Doppler was previously reported in various studies [20,29,30]. We also found that Tei index was more sensitive than left or right ventricle fractional shortening in detecting impaired cardiac performance.…”
Section: /9supporting
confidence: 86%
See 1 more Smart Citation
“…Tissue Doppler was able to detect both systolic and diastolic dysfunction than conventional Doppler in infants of diabetic mothers with hypertrophic cardiomyopathy when compared to the control group. This higher sensitivity of tissue Doppler over the conventional Doppler was previously reported in various studies [20,29,30]. We also found that Tei index was more sensitive than left or right ventricle fractional shortening in detecting impaired cardiac performance.…”
Section: /9supporting
confidence: 86%
“…Hypertrophic cardiomyopathy was diagnosed when the absolute values of inter ventricular septum and left ventricular posterior wall diameters were above normal ranges, and in addition, the ratio of left ventricular septum in diastole to the left ventricular posterior wall in diastole exceeded 1.3 [20].…”
Section: /9mentioning
confidence: 99%
“…Forty-one datasets with 2084 patients were eligible for the meta-analysis of GLS or LS ; 7-24,26-34,36-49 26 datasets with 1506 patients were eligible for the meta-analysis of GCS or CS , 7,9,11,12,14-20,23,25,26,28-31,33,34,41-44,46,48 and 15 datasets with 1092 patients were eligible for the meta-analysis of GRS or RS. 11,15,16,19,20,23,25,26,28,29,33,41-43,46 The patient characteristics of the included studies are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies used a deformation imaging acquisition and post-processing protocol. Reproducibility analysis was performed in 32/43 7-10,14-21,23-27,33,35-46,48,49 datasets and referenced in 4/43. 11,30,31,47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation